POLA PEMBINAAN KARAKTER PANCASILA DI PONDOK PESANTREN MATHLA"™UL ANWAR DI KOTA PONTIANAK - pratama, andi wijaya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The results of this study aim to be able to find out the pattern of Pancasila character development at the Mathla'ul Anwar Islamic Boarding School, Pontianak City. The method used in this research is descriptive with a qualitative approach. The data sources in this study were PPKn teachers, Santri, Heads of Islamic Boarding Schools. Data collection techniques in the form of observation, interviews, and documentation. Data analysis techniques in the form of data collection, data reduction, data presentation, and drawing conclusions. The results showed that the Pancasila character building program consisted of praying 5 times a day, reading the Koran, discipline, and exemplary. Implementation of Pancasila character development carried out at Islamic boarding schools, namely the allocation of time in the form of teaching and learning time for students at Islamic boarding schools, such as extracurricular activities, community service, and the design of teaching materials for activities of Sufism, monotheism, and interpretation, while the description of the Pancasila character of the Santri is the daily habits day, greeting the coach, togetherness and kinship to friends at the Mathla'ul Anwar Islamic Boarding School.